Social representations and educational guidance of the professorship - San Román, Sonsoles; Vecina, Carlos; Usategui, Elisa; del Valle, Ana Irene; Venegas, Mar (Education Policy Analysis Archives, 2015)
In this article we report on the theoretical and methodological approach of a recent research project on the social and cultural representations that affect teachers in the teaching and practice guiding function[1], as well as previous studies whose results that we have supported to advance our hypotheses. Our approach starts from the consideration that social transformations and their influence on the school favor an uncertain environment for teachers, that key social representations guide teachers’ performance in relation to the students, and that schools exercise some degree of determination over the educational guidance that teachers provide. This essay aims to analyze the guidance deployed and practiced by teachers from a sociological perspective, identifying possible approaches and models to explain educational guidance as a socially-constructed phenomenon. [1] This is an R + D + I, Socioeconomic and Educational and Vocational Guidance Teacher of Secondary, approved by the Ministry of Economy and Competitiveness (Spain), for implementation during the 2014-2017 period, with reference CSO2013-47168-R, under the direction of principal researcher Sonsoles San Roman Gago (Autonomous University of Madrid).